PENYELESAIAN SENGKETA JAMINAN DI KOPERASI SIMPAN PINJAM CREDIT UNION BINA SEROJA - Nuli Marmanti; Supri Abu (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
Savings and Loans Cooperatives (Koperasi Simpan Pinjam) play a crucial role in supporting financial access for communities through a system of borrowing and lending based on mutual cooperation and familial principles. However, in practice, many cooperatives face significant challenges when members default, particularly in the execution of collateral which often fails to be carried out effectively. This issue is also evident in the case of the Credit Union Bina Seroja Savings and Loans Cooperative, where obstacles in executing collateral have frequently led to disputes between members and cooperative management. This study aims to identify the main causes behind the failure of collateral execution and to analyze the methods of dispute resolution that can be applied, whether through litigation or non-litigation avenues. The research employs a normative legal method (yuridis normatif), focusing on the analysis of statutory legal norms. The primary legal sources used in this study include the 1945 Constitution of the Republic of Indonesia Article 33 paragraph (1), Law No. 25 of 1992 on Cooperatives, Law No. 4 of 1996 on Mortgage Rights over Land, Law No. 42 of 1999 on Fiduciary Security, Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, as well as relevant articles in the Indonesian Civil Code (KUHPerdata), Ministerial Regulations concerning cooperatives, and internal cooperative regulations such as the Articles of Association (AD/ART) and loan agreements. The findings reveal that weak legal formalities in collateral agreements, lack of legal literacy among cooperative administrators, and the absence of proper legal registration for collateral are key factors hindering the execution process. Additionally, cooperatives have not fully utilized alternative dispute resolution mechanisms such as internal mediation or cooperative arbitration, despite the existence of a sufficient legal framework to support such methods. The study concludes that resolving collateral disputes within cooperatives requires strengthening the legal foundations of collateral agreements and promoting the use of non-litigation dispute resolution methods rooted in cooperative principles, thereby reducing dependency on lengthy and costly court proceedings.